Italy : Financial Sector Assessment Program; Detailed Assessment of Observance of the IMF Code of Good Practices on Transparency in Monetary and Financial Policies; Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2006)
This paper discusses a Detailed Assessment of the Observance of the IMF Code of Good Practices on Transparency in Monetary and Financial Policies (MFPT Code)-Banking Supervision for Italy. Banca d'Italia (BI) notes the assessment's recognition of the very high degree of compliance of the Italian banking supervisory system with MFPT Code. The assessment highlights positive features as the extensive information on banking supervision made publicly available through the annual report and other modes. BI cooperates with other domestic and foreign financial agencies in day-to-day activities through exchange of information and coordinated action.